Объяснение:
1 . 1) ( a + 4 )² = a² + 8a + 16 ; 2) ( 3y - c )² = 9y²- 6yc + c² ;
3) ( 2a - 5 )( 2a + 5 ) =4a² - 25 ; 4) ( x² + y )( x² - y ) = x⁴ - y² .
2 . 1) 0,36 - c² = ( 0,6 - c)( 0,6 + c ) ; 2) a² + 10a + 25 = ( a + 5 )² .
3 . ( a - 2b )² + 4b(a - b ) = a² - 4ab + 4b² + 4ab - 4b² = a² ;
якщо а = 0,12 ; b = 1 , то а² = 0,12² = 0, 0144 .
4 . a) 3( 1 + 2xy )( 1 - 2xy ) = 3( 1 - 4x²y² ) = 3 - 12x²y² ;
б) ( a + b )² - ( a - b )² = a² + 2ab + b² - a² + 2ab - b² = 4ab ;
в) ( x² - y³ )² = x⁴ - 2 x²y³ + y⁶ .
Поделитесь своими знаниями, ответьте на вопрос:
Вычислите значение выражения: 2/7c - 0, 2d при c=-28, d=15
1) 2/7*(-28)=-2/7*28/1=-56/7=-8
2) 0,2*15=2/10*15/1=30/10=3
3) -8-3=-11